2015
DOI: 10.1108/ijqrm-02-2013-0035
|View full text |Cite
|
Sign up to set email alerts
|

The determinants for sustainability of an employee suggestion system

Abstract: Purpose – Although the corporations widely use the suggestion schemes to elicit the creative ideas of their employee, sustaining a suggestion scheme is still a challenge. Employee suggestion schemes have been studied from many perspectives to illustrate its objectives, nature, content, process, significance and the benefits. Arguments have also been made with respect to the success and failures of the suggestion schemes. The purpose of this paper is to explore the factors to assess the sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(61 citation statements)
references
References 93 publications
2
57
0
Order By: Relevance
“…This paper addresses the call for research proposed by several authors to take into consideration individual attributes in the ESS process to enhancing performance in organizations (Carrier, 1998;Griffiths-Hemans and Grover, 2006;Gupta and Banerjee, 2016;Marin-Garcia et al, 2018;Marksberry et al, 2014;Shalley and Gilson, 2004;McAdam and McClelland, 2002;Moneim, 2009;Prado-Prado et al, 2018;Van Dijk and Van den Ende, 2002). Previous studies carried out in United Arab Emirates (UAE) have largely overlooked individual characteristics or attributes, such as cognitive skills, personal characteristics, domain-relevant skills, which constitute the idea generation process and largely concentrated on success factors from organizational perspective (Arif et al, 2010;Lasrado et al, 2015Lasrado et al, , 2017Moneim, 2009). With the growing emphasis on emerging economies, placed on innovation and creativity in the knowledge economy, the study was an attempt to unravel both individual-level factors and organizational factors that promote ESS and to prioritize them to improve performance and corporate health in the complex work setting by actively involving employees.…”
Section: Antecedents To Employee Suggestion Schemes 497mentioning
confidence: 99%
See 1 more Smart Citation
“…This paper addresses the call for research proposed by several authors to take into consideration individual attributes in the ESS process to enhancing performance in organizations (Carrier, 1998;Griffiths-Hemans and Grover, 2006;Gupta and Banerjee, 2016;Marin-Garcia et al, 2018;Marksberry et al, 2014;Shalley and Gilson, 2004;McAdam and McClelland, 2002;Moneim, 2009;Prado-Prado et al, 2018;Van Dijk and Van den Ende, 2002). Previous studies carried out in United Arab Emirates (UAE) have largely overlooked individual characteristics or attributes, such as cognitive skills, personal characteristics, domain-relevant skills, which constitute the idea generation process and largely concentrated on success factors from organizational perspective (Arif et al, 2010;Lasrado et al, 2015Lasrado et al, , 2017Moneim, 2009). With the growing emphasis on emerging economies, placed on innovation and creativity in the knowledge economy, the study was an attempt to unravel both individual-level factors and organizational factors that promote ESS and to prioritize them to improve performance and corporate health in the complex work setting by actively involving employees.…”
Section: Antecedents To Employee Suggestion Schemes 497mentioning
confidence: 99%
“…Literature review and theoretical framework ESS is not a new concept. Literature from past studies has widely commented on the history, nature, goals, and evolution of ESS (Carrier, 1998;Lasrado et al, 2015). Moreover, ESS has a considerable history in Europe, America, Middle East, and Asia and has been researched by several authors (Arif et al, 2010;Carrier, 1998;Lasrado et al, 2015).…”
Section: Tqm 323mentioning
confidence: 99%
“…Therefore, some top managers choose to not adopt EDIs in their firms. Although in firms that have adopted EDIs, it has been found that the firms' design and use of their suggestion systems are different, and therefore the system does not work in some firms [40,43]. Top managers' decision making is a key determinant to a firm's adoption of innovative management practices [44], thus, whether the suggestion system works or not is highly influenced by characteristics of managers in top positions.…”
Section: Employee-driven Innovationsmentioning
confidence: 99%
“…Similarly, to assess the sustainability of a suggestion scheme, the key elements that focus on these perspectives need to be considered. Lasrado et al (2015a) defined the sustainability of a suggestion scheme as "The achievement of stakeholder's stated goals involving competence management, profitability, employee productivity and continuous process improvement now and in the future".…”
Section: Defining the Sustainability Of Employee Suggestion Schemementioning
confidence: 99%
“…Further, the variables emerging from the literature that foster suggestion scheme are: top management support, supervisor encouragement, coworker support, organizational encouragement, support for innovation, communication evaluation, awareness, resources, rewards, training, effective system, feedback, implementation of ideas, empowerment, job factors, expertise, self-efficacy and individual characteristics, teamwork, employee participation, job control, organizational impediments and the competition, employee confidence, sense of security, commitment and accountability, improvement in process, customer satisfaction, product quality, new revenue, cost 429 Employee suggestion schemes saving, employee satisfaction (Lasrado et al, 2015a). Also, there are typical pitfalls noted in the literature which would impact suggestion schemes negatively.…”
Section: Defining the Sustainability Of Employee Suggestion Schemementioning
confidence: 99%